Women on Finnish dairy farms : Hard work in the midst of traditions and changes - Kallioniemi, Marja; Kymäläinen, Hanna-Riitta (eContent Management, 2012)
This research focuses on the work, working conditions and role of women on dairy farms in the context of agricultural change and traditions. The qualitative, case study sample is comprised of work observations and interviews of women on ten dairy farms. The women typically worked on the farm as a consequence of marriage or courtship with a farmer, and most selected 'farm entrepreneurŽ as their professional title. Women were involved in a wide range of different work tasks, mainly in cattle barns and at home. It was observed that whereas men operated machinery in cattle barns, women performed physical, manual work tasks. One of women's tasks was to monitor and take care of the health and living conditions of farm animals. Nearly all the women considered work with animals and being 'close to nature' rewarding, but half assessed the workload as too heavy. General strategies used to avoid exhaustion were to employ salaried workers, utilise networks and/or use contractors. Nearly all respondents had experienced some kind of problems related to organising absence from farm work during sickness or holidays. To improve womenŽs work situation and facilitate their valuable contribution to agriculture, this article concludes by offering a number of suggestions to inform future research and practices. Keywords
Keywords: Ma; Finland; lypsykarjatilat; naiset; agriculture; dairy farms; women; working conditions; työolot